Teknologi Pendidikan Pada Pembelajaran Abad 21 di Pendidikan Dasar - Hasibuan, Barumun Parulian; Harida, Eka Sustri (Sekolah Tinggi Ilmu Tarbiyah Padang Lawas (STIT PL) Gunung Tua, 2025)
Indonesia is a nation endowed with competent and skilled human resources. As a developing country, Indonesia faces many challenges that must be addressed. One of the greatest challenges comes from the Indonesian education sector, which must continuously adapt to technological advancements, particularly in the field of education. Educational technology in Indonesia plays a vital role in advancing 21st-century learning. Twenty-first-century learning refers to teaching and learning processes between educators and students that integrate information and communication technology. This approach also requires educators to be prepared to shift learning models and instructional strategies from those that are teacher-centered to approaches that are student-centered. To achieve 21st-century learning in basic education, educators must serve as the main driving force in education and play a crucial role in integrating technology into the learning process. Through the integration of technology in every learning activity, along with support from parents, school principals, and the government, it is expected that a young generation will be produced that is intelligent, has strong character, and is ready to face the Era 5.0.